Endoscopic management of canine pyometra: Report and discussion of a case - Salvo Briceño, Claudio (2023)
The case of a 15-month-old Alaskan Malamute bitch, presented for purulent vaginal discharge and weakness, approximately 2 to 3 weeks after estrus, is described. In the clinical and ultrasound evaluation, open cervix pyometra was diagnosed, and considering the age of the female, as well as her genetic value, a therapy is established that included antibiotics, aglepristone and intrauterine lavage with ozonated serum via endoscopy. The recovery of the patient was achieved in a short time.